Case report: Congenital absence of the dens - Bajaj, Manish; Jangid, Hemant; Vats, AK; Meena, ML (Indian Journal of Radiology and Imaging, 2010)
A 36-year-old man presented with headache and right upper and lower limb weakness for 10 days. MRI revealed absence of the odontoid process of the C2 vertebral body, with resultant atlantoaxial dislocation along with myelomalacic changes involving the cervicomedullary junction.
Keywords: Absent; congenital; dens